2023
DOI: 10.3389/fpsyg.2023.1099399
|View full text |Cite
|
Sign up to set email alerts
|

“The show must go on”: How Paralympic athletes safeguarded their mental well-being and motivation to train for the postponed Tokyo 2020 games

Abstract: IntroductionAfter the decision to postpone the Tokyo 2020 Games due to the COVID-19 pandemic, athletes had to adjust to a novel situation with feelings of uncertainty and insecurity. Grounded in Self-Determination Theory, this study was the first to examine whether different motivational profiles among Paralympic athletes can be identified, and to link these profiles with the athletes’ emotional, cognitive, and performance-related outcomes in times of a pandemic.MethodsFive months before the start of the Paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…It is also important to note that coping effectiveness during this period might have been influenced by other factors not explored in these studies. Factors like motivation can drive engagement, including participation in physical activities and sports and the capability to overcome pandemic-related barriers ( Han et al, 2021 ; Silva et al, 2022 ; Van Biesen and Morbee, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that coping effectiveness during this period might have been influenced by other factors not explored in these studies. Factors like motivation can drive engagement, including participation in physical activities and sports and the capability to overcome pandemic-related barriers ( Han et al, 2021 ; Silva et al, 2022 ; Van Biesen and Morbee, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, other research has shown that if someone is motivated by outside rewards or pressures, it can actually make their sports performance worse by taking away their independence, skill, and connection to others. Another study by Van Biesen & Morbee (2023) found that extrinsic motivation was negatively related to swimming performance by undermining self-regulation and psychological needs.…”
mentioning
confidence: 99%